Faktor-Faktor yang Berhubungan dengan Kepatuhan Penggunaan Alat Pelindung Diri bagi Pekerja Kontraktor pada PT X - Ahmad Farhan Mubarak; Ida Umarul Mufidah; Eka Fitriani Ahmad (POLITEKNIK KETENAGAKERJAAN, 2025)
Compliance with the use of Personal Protective Equipment (PPE) is a crucial aspect in the implementation of Occupational Safety and Health (K3), especially in the high-risk construction sector. Although the regulations of Law No. 1 of 1975 and Regulation of the Minister of Manpower No. 8 of 2010 have mandated the use of PPE, the violation rate is still quite high among contractor workers. This study aims to analyze factors related to compliance with the use of PPE among contractor workers at PT X. The research design used a quantitative approach with a cross-sectional method, involving 75 respondents selected through a total sampling technique. Data were collected through a closed questionnaire that had been validated and tested for reliability. The results of the chi-square analysis showed that there was a significant relationship between supervision and compliance with the use of PPE (p = 0.000), while individual characteristic variables such as age (p = 0.673), education (p = 0.251), and length of service (p = 0.841) did not show a significant relationship. These findings reinforce Lawrence Green's Precede-Proceed theory, which emphasizes the importance of predisposing and reinforcing factors in shaping health behaviors. Therefore, increasing the effectiveness of supervision, coupled with a coaching approach tailored to worker characteristics, can be a strategy for improving compliance with PPE use. Future research is recommended to further explore the role of organizational factors and work culture in PPE compliance behavior.